2023
DOI: 10.1096/fj.202201977r
|View full text |Cite
|
Sign up to set email alerts
|

Machine‐learning methods applied to integrated transcriptomic data from bovine blastocysts and elongating conceptuses to identify genes predictive of embryonic competence

Abstract: Early pregnancy loss markedly impacts reproductive efficiency in cattle. The objectives were to model a biologically relevant gene signature predicting embryonic competence for survival after integrating transcriptomic data from blastocysts and elongating conceptuses with different developmental capacities and to validate the potential biomarkers with independent embryonic data sets through the application of machine-learning algorithms. First, two data sets from in vivoproduced blastocysts competent or not to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 67 publications
(142 reference statements)
1
9
0
Order By: Relevance
“…Subsequently, we integrated the genes from the LASSO, SVM-REF, and MCODE modules to obtain three important genes. Finally, a diagnostic model was developed using five machine learning techniques, including logistic regression [ 33 ], Bayesian logistic regression [ 34 ], decision tree [ 35 ], random forest [ 36 ], and extreme gradient boosting [ 37 ], to evaluate the diagnostic value of these three genes in TB disease.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, we integrated the genes from the LASSO, SVM-REF, and MCODE modules to obtain three important genes. Finally, a diagnostic model was developed using five machine learning techniques, including logistic regression [ 33 ], Bayesian logistic regression [ 34 ], decision tree [ 35 ], random forest [ 36 ], and extreme gradient boosting [ 37 ], to evaluate the diagnostic value of these three genes in TB disease.…”
Section: Methodsmentioning
confidence: 99%
“…Determining markers of embryo competence to establish a pregnancy has been the focus of much research as it has the potential to improve the efficiency of ART by enabling the early prediction of which embryos are more likely to survive to term. Recently, Rabaglino et al (2023) combined the integration of transcriptomic datasets with the use of machine learning to predict embryo competence and survival. The authors reported a subset of eight genes, namely GSTO1, CHSY1, TPI1, YWHAG, CCNA2, LSM4, CDK7, and EIF4A3, which predicted with high accuracy the competence of embryos in different datasets, indicating that these genes might be important biomarkers of embryo competence.…”
Section: Potential Novel Markers Of Embryo Competencementioning
confidence: 99%
“…ML approaches have recently become popular as a method of analysing large, complex omics-based datasets. Rabaglino et al (2023) combined Bayesian logistic regression and neural network models with bovine transcriptomic data to identify eight genes whose expression was predictive of conceptus competence. In addition, the development of ML approaches, such as in Christmas et al (2023), have led to finding enhancer regions associated with phenotypic differences in mammals, with many of the most highly conserved regions associated with embryonic development.…”
Section: In Silico Approachesmentioning
confidence: 99%